The generation of Ganymede's diffuse aurora through pitch angle scattering - Tripathi A.K.; Singhal R.P.; Singh O.N., II (My University, 2025)
Diffuse auroral intensities of neutral atomic oxygen OIa;1356Å emission on Ganymede due to whistler mode waves are estimated. Pitch angle diffusion of magnetospheric electrons into the loss cone due to resonant wave-particle interaction of whistler mode waves is considered, and the resulting electron precipitation flux is calculated. The analytical yield spectrum approach is used for determining the energy deposition of electrons precipitating into the atmosphere of Ganymede. It is found that the intensities (4-30R) calculated from the precipitation of magnetospheric electrons observed near Ganymede are inadequate to account for the observational intensities (≤100R). This is in agreement with the conclusions reached in previous works. Some acceleration mechanism is required to energize the magnetospheric electrons. In the present work we consider the heating and acceleration of magnetospheric electrons by electrostatic waves. Two particle distribution functions (Maxwellian and kappa distribution) are used to simulate heating and acceleration of electrons. Precipitation of a Maxwellian distribution of electrons can produce about 70R intensities of OIa;1356Å emission for electron temperature of 150eV. A kappa distribution can also yield a diffuse auroral intensity of similar magnitude for a characteristic energy of about 100eV. The maximum contribution to the estimated intensity results from the dissociative excitation of O2. Contributions from the direct excitation of atomic oxygen and cascading in atomic oxygen are estimated to be only about 1 and 2% of the total calculated intensity, respectively. The findings of this work are relevant for the present JUNO and future JUICE missions to Jupiter. These missions will provide new data on electron densities, electron temperature and whistler mode wave amplitudes in the magnetosphere of Jupiter near Ganymede. © 2017 The Author(s).